Genome-Wide Analysis of microRNA and mRNA Expression in Colorectal Intramucosal Neoplasia and Colorectal Cancer With a Microsatellite-Stable Phenotype Based on Adenoma-Carcinoma Sequences - Sugai, Tamotsu; Osakabe, Mitsumasa; Niinuma, Takeshi; Sugimoto, Ryo; Eizuka, Makoto; Tanaka, Yoshihito; Yanagawa, Naoki; Otsuka, Koki; Sasaki, Akira; Matsumoto, Takayuki; Suzuki, Hiromu (Frontiers in Oncology, 2022)
Background Although MicroRNAs (miRNAs) play important roles in various biological processes, the biological functions of miRNAs are achieved through mRNAs. The aim of this study is to identify dysregulated miRNA/mRNA expression patterns in colorectal tumors. Methods We examined 42 colorectal tumors [15 adenomas, 8 intramucosal cancers (IMCs), and 19 invasive colorectal cancers (CRCs)] with the microsatellite stable (MSS) phenotype (first cohort). The first cohort was used for genome-wide miRNA and mRNA expression arrays, whereas the second cohort (37 colorectal neoplasias) was used for validation analyses. Finally, we used 15 cases of “adenoma in/with carcinoma” to identify network patterns of miRNAs/mRNAs that were directly associated with neoplastic progression. In addition, simple regression analysis for array-based and RT-PCR analyses was performed to select candidate miRNA–mRNA pairs. Transfection of miRNA mimics was also performed to confirm whether target mRNA expression is affected by specific miRNAs. Results Specific paired miRNA/mRNA networks, including hsa-miR-34a-5p/SLC12A2, hsa-miR-15b-5p/SLC12A2, hsa-miR-195-5p/SLC12A2, hsa-miRNA-502-3p/OLFM4, hsa-miRNA-6807-5p/ZG16, and hsa-miRNA 3064-5p/SH3BGRL3, were identified in samples of adenoma, IMC, and CRC with the MSS phenotype. In adenomatous lesions obtained from the same tumor with a carcinomatous lesion, we identified pairs of miRNA-130a-3p/HSPA8 and miRNA-22-3p/RP53 that were linked to multiple pathways. On the other hand, 2 pairs of miRNA/mRNA (miRNA-660-5p and miRNA-664a-5p/APP) were found in isolated carcinomatous glands. Ectopic expression of miRNA 3064-5p suppressed SH3BGRL3 expression. Conclusions We found that networks based on specific pairs of miRNAs/mRNAs contribute to progression from adenomatous and carcinomatous lesions. Our results provide insights into the molecular tumorigenesis of colorectal tumors.